Update on percutaneous mitral commissurotomy. Issue 7 (7th January 2016) - Nunes, Maria Carmo P; Nascimento, Bruno Ramos; Lodi-Junqueira, Lucas; Tan, Timothy C; Athayde, Guilherme Rafael Sant'Anna; Hung, Judy
Abstract : Percutaneous mitral commissurotomy (PMC) is the first-line therapy for managing rheumatic mitral stenosis. Over the past two decades, the indications of the procedure have expanded to include patients with unfavourable valve anatomy as a consequence of epidemiological changes in patient population. The procedure is increasingly being performed in patients with increased age, more deformed valves and associated comorbidities. Echocardiography plays a crucial role in patient selection and to guide a more efficient procedure. The main echocardiographic predictors of immediate results after PMC are mitral valve area, subvalvular thickening and valve calcification, especially at the commissural level. However, procedural success rate is not only dependent on valve anatomy, but a number of other factors including patient characteristics, interventional management strategies and operator expertise. Severe mitral regurgitation continues to be the most common immediate procedural complication with unchanged incidence rates over time. The long-term outcome after PMC is mainly determined by the immediate procedural results. Postprocedural parameters associated with late adverse events include mitral valve area, mitral regurgitation severity, mean gradient and pulmonary artery pressure. Mitral restenosis is an important predictor of event-free survival rates after successful PMC, and repeat procedure can be considered in cases with commissural refusion. PMC can be performed in special situations, which include high-risk patients, during pregnancy and in the presence of left atrial thrombus, especially in centres with specialised expertise. Therefore, procedural decision-making should take into account the several determinant factors of PMC outcomes. This paper provides an overview and update of PMC techniques, complications, immediate and long-term results over time, and assessment of suitability for the procedure.